2006
DOI: 10.1134/s1063778806120155
|View full text |Cite
|
Sign up to set email alerts
|

Scintillating double-beta-decay bolometers

Abstract: We present the results obtained in the development of scintillating Double Beta Decay bolometers. Several Mo and Cd based crystals were tested with the bolometric technique. The scintillation light was measured through a second independent bolometer. A 140 g CdWO 4 crystal was run in a 417 h live time measurement. Thanks to the scintillation light, the α background is easily discriminated resulting in zero counts above the 2615 keV γ line of 208 Tl. These results, combined with an extremely easy light detector… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
193
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 158 publications
(197 citation statements)
references
References 16 publications
4
193
0
Order By: Relevance
“…The particle identification comes then from the different light yield for different particle type. For scintillating crystals such as ZnSe, CdWO 4 , and ZnMoO 4 , the light yield difference between possible β β (0ν) electrons and α particles have been measured [41] and the background suppression concept demonstrated. It is worth noticing that the natural isotopic abundance of 82 Se, 116 Cd and 100 Mo are all less than 10 % so that isotopic enrichment is mandatory.…”
Section: Prospectsmentioning
confidence: 99%
“…The particle identification comes then from the different light yield for different particle type. For scintillating crystals such as ZnSe, CdWO 4 , and ZnMoO 4 , the light yield difference between possible β β (0ν) electrons and α particles have been measured [41] and the background suppression concept demonstrated. It is worth noticing that the natural isotopic abundance of 82 Se, 116 Cd and 100 Mo are all less than 10 % so that isotopic enrichment is mandatory.…”
Section: Prospectsmentioning
confidence: 99%
“…To this end, additional detection channels are needed, since the absorber does not respond differently for energy releases of different particle types. To distinguish signal electrons from α background, light emission can be used, either from Cherenkov radiation [22,23] or scintillation light [24,25,28,29], where the auxiliary light detector is usually another bolometer facing the main one. Recently new studies on scintillating bolometers showed the possibility to distinguish α from β/γ particles without light readout thanks to a different time-dependent shape of the heat signal [30,31].…”
Section: Beyond Cuorementioning
confidence: 99%
“…The arguments to develop CaMoO 4 are as follows: 100 Mo is one of the most promising candidate to search for neutrinoless double beta decay (a key process in the modern physics) [34]; CaMoO 4 contains valuable part of Mo (48%); CaMoO 4 does not contain radioactive elements; CaMoO 4 is a reasonably ecient scintillator even at room temperature [35]; CaMoO 4 is a promising material for low temperature scintillating bolometers (with high energy resolution and particle discrimination ability) [36,37].…”
Section: Yttrium Aluminum Perovskitementioning
confidence: 99%